Formulasi Etika Kecerdasan Buatan (AI) Dalam Pendidikan Islam: Pendekatan Maqāṣid al-Sharī‘ah dan Tafsir Tematik Al-Qur’an - Supriatin, Iit; Syarifah, Siti; Susilawati, Ela; Supriadi, Iki; Apriani, Risa (Halaqa: Journal of Islamic Education, 2025)
This study explores the ethical utilization of Artificial Intelligence (AI) in Islamic education through an integrative approach that combines maqāṣid al-sharī‘ah and thematic Qur’anic exegesis. This research aims to formulate a contextual and applicable Islamic ethical framework for the use of AI in learning processes. Employing a qualitative library research method, data were collected from primary sources (Qur’anic verses and tafsir) and secondary sources (academic journals, books, institutional reports). The findings reveal that AI can support Islamic education when ethically guided—by upholding the protection of religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and lineage (ḥifẓ al-nasl). The study also articulates three core Qur’anic ethical principles—reason as wisdom, knowledge as divine trust, and moral accountability (amānah)—as the basis for AI development. The novelty of this research lies in integrating two classical Islamic methodologies to address contemporary technological challenges. Its implications span educational technology policy design, ethical guidance for Islamic AI developers, and teacher training curriculum for the digital era.